2021
DOI: 10.1155/2021/6067678
|View full text |Cite
|
Sign up to set email alerts
|

Application of Adaptive Virtual Reality with AI-Enabled Techniques in Modern Sports Training

Abstract: Virtual reality technology has many characteristics, such as high immersion, dynamic interactive response, and multidimensional information digitization. These characteristics are needed by the combination of modern sports development and scientific and technological progress. The introduction of virtual reality technology into the field of sports will be conducive to the scientific training of sports competition and the digital research of technical theory and to the rapid development of modern sports. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Besides, VR can enhance trainees' performance in archery and boxing. Zhang and Tsai (2021) 2021) introduced the virtual aRCheRy platform, a VR archery game. The platform was equipped with a pipeline using its own sensor fusion algorithms to analyze both spatial performance and motor behavior.…”
Section: Skill Acquisition and Technique Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, VR can enhance trainees' performance in archery and boxing. Zhang and Tsai (2021) 2021) introduced the virtual aRCheRy platform, a VR archery game. The platform was equipped with a pipeline using its own sensor fusion algorithms to analyze both spatial performance and motor behavior.…”
Section: Skill Acquisition and Technique Trainingmentioning
confidence: 99%
“…Besides, VR can enhance trainees’ performance in archery and boxing. Zhang and Tsai (2021) presented a sports training framework based on VR and a motion capture data algorithm. The training experiment results demonstrated that the VR training method could stimulate students’ interest in training, improve their training effect and promote their psychological internal motivation to continue training.…”
Section: Enhanced Physical Training Through Sensor Fusion-based Virtu...mentioning
confidence: 99%
“…It was found that the student was greatly impressed by the usage of the modern technique and his interest in tennis learning was enhanced. The study showed that based on virtual reality, a very effective and e cient training atmosphere can be developed for the training of new learners [22]. The aggression shown by the players during sports can result in some serious situations and can affect the quality of sports.…”
Section: Dss For Action Recognition Of Track and Field Sports Using Acomentioning
confidence: 99%